Employee Turnover of Quantity Surveying Firms in Malaysia - Habizah Sheikh Ilmi; He Xue Qi; Mariatul Liza Meor Gheda
Employees are important stakeholders in any firm. There is a trend of a high employee turnover rate in many firms in the construction industry. However, there is lack of emphasis on the reasons of employee turnover especially in the quantity surveying (QS) firms in Malaysia. The purpose of this paper is to examine the factors that contribute to turnover and its impact to the quantity surveying consultant firms. The data was collected by distributing survey questionnaires to employees of QS firms to obtain their views on the subject matter. From the analysis, the factors that caused employee turnover were established. Three quarters of respondents replied that their firms are experiencing staff turnover and the most significant impact to the firms is that they are losing their experienced quantity surveyors. In addition, QS staffs are dissatisfied to their current salary and this factor causes them to seek for a higher pay in other firms or places.(Abstract by authors)